Computational Study of Cold-Formed-Steel X-Braced Shear Walls - Metwally Abu-Hamd; Maheeb Abdel-Ghaffar; Basel El-Samman (Advances in Civil Engineering)
The aim of this paper was to present a verified finite element method that represents the full-scale-braced shear walls under seismic loads and to study their ductility. The models account for different types of material and geometric nonlinearities. The screws that connect the cold-formed-steel (CFS) studs, tracks, gusset plates, and braces are considered explicitly in the model. The deformation of the hold-downs under the horizontal load is considered. The finite element program ANSYS (2012) is used to model and analyze the case studies. A parametric study is performed to investigate the response modification factor (R) of the CFS-braced shear walls. The parametric study showed that the North American Specification is about 20% conservative in estimating the (R) factor.